Analysis of Coastal Community Health Vulnerability in Facing Climate Change in Mata Urban Village, Kendari District, Kendari City, Southeast Sulawesi Province, Indonesia - Ramadhan Tosepu; Putri Yuliyanti Liambo; Zahwa Nizar; Siti Selfia; Waode Monang; Ade Sriwahyuni; Adrian; Sri Anawati; Fitra Wati; Syarah Wahyuni Iriadi (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Coastal communities are populations residing in coastal areas who develop distinct socio-cultural characteristics shaped by their reliance on coastal resources and ecosystems. These communities are particularly vulnerable to the adverse effects of climate change, which include rising sea surface temperatures, increased intensity and frequency of extreme weather events, altered precipitation patterns, and the intensification of oceanic wave activity. Such climatic changes pose significant threats to the sustainability and well-being of coastal populations. Objective: This study aims to analyze the health vulnerability of coastal communities in response to climate change, with a focus on Mata Subdistrict, Kendari District, in the year 2024. Methods: A cross-sectional analytical design was employed in this study. A total of 200 respondents were selected from Mata Subdistrict, Kendari District, using purposive sampling. Data were collected through structured interviews utilizing validated questionnaires, alongside direct field observations. The data were subsequently analyzed using univariate and bivariate statistical methods with the assistance of SPSS version 25. Results: The socio-demographic analysis revealed that the majority of respondents were female (55.5%, n=111), while males accounted for 44.5% (n=89). Most respondents were aged between 31 and 40 years. The largest proportion of marital status indicated married individuals (52%, n=104), and the most common household size was five members (29%, n=58). Bivariate analysis showed statistically significant associations between the incidence of illness and several climate-related variables: experience of coastal erosion in the past five years (p=0.047), exposure to strong winds within the same period (p=0.006), and health insurance ownership (p=0.007). Conclusion: This study highlights the health vulnerability of coastal communities in Mata Subdistrict, Kendari District, due to climate change. The findings indicate that vulnerability is influenced by a complex interplay of demographic, economic, infrastructural, environmental, and health-related factors, as well as by the community’s adaptive capacity and the availability of external support mechanisms. Keywords: Climate Change, Coastal Communities, Health Vulnerability, Mata Subdistrict, Kendari District